Pengaruh Kompetensi Integrasi Teknologi, Konten Dan Pedagogik (TPACK), Motivasi Kerja Dan Teachers’ Work Engagement Terhadap Kinerja Guru SD XYZ Cabang Bekasi - Widowati, Priskalia Niken; Purbojo, Rijanto (Cetta: Jurnal Ilmu Pendidikan, 2024)
Teachers are one of the most important elements in educational institutions. Along with advances in technology, teachers play an important role in education. Teacher performance is influenced by other factors such as Technological Pedagogical Content Knowledge (TPACK), work motivation and teacher's work engagement. This research aims to determine the influence of Technological Pedagogical Content Knowledge (TPACK), Work Motivation and Teacher's Work Engagement toward Teacher Performance. The research subjects were 121 teachers at XYZ Elementary School, Bekasi Branch. Data was collected through distributing a questionnaire consisting of 92 questions using a five-point Likert scale. Data analysis uses SmartPLS 3.0 and the approach used is Structural Equation Modeling (SEM)-Partial Least Square. In this research, it was found that technology, content and pedagogical integration competence (TPACK) and work motivation had a positive and significant influence on teacher performance. However, one variable, namely teachers' working engagement, has a positive but not statistically significant relationship with teacher performance.